2017
DOI: 10.1007/s12032-017-0944-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeted next-generation sequencing identified novel mutations in triple-negative myeloproliferative neoplasms

Abstract: Mutations in JAK2, MPL and CALR genes have been identified in the majority of myeloproliferative neoplasm (MPN) patients, and patients negative for these three mutations are the so-called triple-negative (TN) MPN. In this study, we examined the mutational profiles of 16 triple-negative MPN patients including 7 essential thrombocythemia (ET), 1 primary myelofibrosis and 8 polycythemia vera (PV). Targeted next-generation sequencing was performed using the ACTOnco Comprehensive Cancer Panel (Ion AmpliSeq Comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Chang Y-Can et al, 45 described an MPLM602T mutation in such a patient. Chang Y-Can et al, 45 described an MPLM602T mutation in such a patient.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Chang Y-Can et al, 45 described an MPLM602T mutation in such a patient. Chang Y-Can et al, 45 described an MPLM602T mutation in such a patient.…”
Section: Discussionmentioning
confidence: 94%
“…Interesting is also the fact that MPL mutations could be found in patients with PV. Chang Y-Can et al, 45 described an MPLM602T mutation in such a patient. In our cohort, an MPLY591D mutation was found in one JAK2V617F positive patient with post-PV-MF (#13, Table 2).…”
Section: Discussionmentioning
confidence: 94%
“…The most frequently affected genes were PDE4DIP , MAP3K1 , CDCEP1 and AFF3 . The PDE4DIP mutation was previously found in myeloproliferative neoplasms and medullary thyroid cancer 42,43 . MAP3K1 encodes a mitogen‐activated protein kinase kinase kinase that is involved in cell survival and apoptosis and was recently found to be related to breast and colorectal cancer 44‐47 .…”
Section: Discussionmentioning
confidence: 80%
“…13 IRS2 mutations were described in triple-negative MPN patients. 19 Osorio et al 20 demonstrated that IGFIR deregulation promotes MPN, incorporating new evidence that the IGF1R/IRS axis is potentially involved in the MPN phenotype and may represent a therapeutic target for these diseases.…”
Section: Introductionmentioning
confidence: 99%